2015
DOI: 10.4300/jgme-d-14-00612.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Restricting Residents' Duty Hours on Patient Safety, Resident Well-Being, and Resident Education: An Updated Systematic Review

Abstract: Background Despite 25 years of implementation and a sizable amount of research, the impact of resident duty hour restrictions on patients and residents still is unclear. Advocates interpret the research as necessitating immediate change; opponents draw competing conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
188
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 54 publications
3
188
1
2
Order By: Relevance
“…25 A recent systemic review demonstrated that focusing on duty hours alone did not result in improvements in patient care or resident well-being and may have had a negative effect on resident education. 26 While work hour limits appear to be effective in reducing burnout rates among resident physicians, further restrictions in work hours may result in the inadequate training of physicians or the lengthening of an already long training period. Some other interventions to address burnout have been suggested, including supportive interventions for internal medicine residents.…”
Section: Discussionmentioning
confidence: 99%
“…25 A recent systemic review demonstrated that focusing on duty hours alone did not result in improvements in patient care or resident well-being and may have had a negative effect on resident education. 26 While work hour limits appear to be effective in reducing burnout rates among resident physicians, further restrictions in work hours may result in the inadequate training of physicians or the lengthening of an already long training period. Some other interventions to address burnout have been suggested, including supportive interventions for internal medicine residents.…”
Section: Discussionmentioning
confidence: 99%
“…Three investigators (PDP, LKB, and MSR) adapted a categorical system used by Bolster and Rourke to describe the impact of a fatigue training intervention on critical and important outcomes as favorable, unfavorable, mixed/inconclusive, or no impact (22). We describe our protocol for categorizing findings in a separate publication (18).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] A systematic review of the effects of the 2003 duty hour requirement on patient safety, resident well-being, and resident education found no impact on patient care or on resident wellbeing. 8 The authors did find an unintended negative impact on resident education, including less time spent with attending physicians and decreased attendance at teaching sessions. 8 There have been several studies examining the effect of the ACGME duty hour requirements on board certification examination performances.…”
Section: Introductionmentioning
confidence: 99%
“…8 The authors did find an unintended negative impact on resident education, including less time spent with attending physicians and decreased attendance at teaching sessions. 8 There have been several studies examining the effect of the ACGME duty hour requirements on board certification examination performances. 4,[9][10][11] The findings have been inconsistent, with improved performance in some specialties, decline in others, and a third group that showed no impact.…”
Section: Introductionmentioning
confidence: 99%